2021
DOI: 10.3390/antiox10020241
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants Promote Intestinal Tumor Progression in Mice

Abstract: Dietary antioxidants and supplements are widely used to protect against cancer, even though it is now clear that antioxidants can promote tumor progression by helping cancer cells to overcome barriers of oxidative stress. Although recent studies have, in great detail, explored the role of antioxidants in lung and skin tumors driven by RAS and RAF mutations, little is known about the impact of antioxidant supplementation on other cancers, including Wnt-driven tumors originating from the gut. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…It was assumed that both vitamin C and vitamin E have low toxicity and were not believed to cause serious adverse effects at much higher intake than needed for their function as vitamins. However, several non-human animal studies showed that antioxidant supplements, including NAC, vitamin E and the soluble vitamin E analogue Trolox, promoted cancer development and metastasis, for example, lung, melanoma and intestinal tumours in mouse models 228 230 . The potential effect of antioxidants on cancer promotion, including the aforementioned NRF2 activators, raises significant concerns regarding the use of antioxidant supplements, and novel strategies are needed to resolve the double-edged effect of antioxidants.…”
Section: Antioxidant Therapeutic Strategiesmentioning
confidence: 99%
“…It was assumed that both vitamin C and vitamin E have low toxicity and were not believed to cause serious adverse effects at much higher intake than needed for their function as vitamins. However, several non-human animal studies showed that antioxidant supplements, including NAC, vitamin E and the soluble vitamin E analogue Trolox, promoted cancer development and metastasis, for example, lung, melanoma and intestinal tumours in mouse models 228 230 . The potential effect of antioxidants on cancer promotion, including the aforementioned NRF2 activators, raises significant concerns regarding the use of antioxidant supplements, and novel strategies are needed to resolve the double-edged effect of antioxidants.…”
Section: Antioxidant Therapeutic Strategiesmentioning
confidence: 99%
“…This is observed in both patient-derived xenografts growing in immunocompromised mice, as well as mouse melanomas growing in syngeneic, immunocompetent mice. Oxidative stress limits the metastasis of other cancers as well (42)(43)(44)(45)(46)(47)(48)(49)(50)(51), though oxidative stress may promote metastasis under certain circumstances (52,53). Large clinical trials found that antioxidant supplementation in humans increases cancer incidence and mortality (54)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…This is observed in both patient-derived xenografts growing in immunocompromised mice as well as mouse melanomas growing in syngeneic, immunocompetent mice. Oxidative stress limits the metastasis of other cancers as well (41)(42)(43)(44)(45)(46)(47)(48)(49)(50), though oxidative stress may promote metastasis under certain circumstances (51,52). Large clinical trials found that antioxidant supplementation in humans increases cancer incidence and mortality (53)(54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%